Digitizing Scientific Qur’anic Exegesis: A Decolonial Analysis of Tafsil.id - Sujiat Zubaidi; Aqdi Rofiq Asnawi; Moh Isom Mudin; Triana Harmini (Buletin Al-Turas, 2026)
Purpose This study examined the Tafsil.id platform as a contemporary digital medium for scientific Qur’anic exegesis, addressing how digital tafsir initiatives in Indonesia reconfigure religious authority and knowledge production within a localized context. Method This research employed a qualitative content analysis of Tafsil.id, focusing on its thematic organization of Qur’anic verses, interpretive sources, and modes of scientific integration. The analysis was informed by relevant literature on scientific exegesis, digital religion, and decolonial perspectives.         Results/findings The findings showed that Tafsil.id localized scientific Qur’anic interpretation through the use of Bahasa Indonesia and thematic structuring, making it more accessible to a wider audience. The platform showed a hybrid epistemic model that combined classical Arabic exegetical sources with contemporary scientific discourse in areas such as cosmology and environmental studies. This configuration expanded access while maintaining continuity with established interpretive traditions. Conclusion This study concluded that Tafsil.id helped to digitally mediate Qur'anic interpretation by increasing access and altering modes of involvement. However, its epistemic transformation was only partial, occurring through a bargain between localization and reliance. The study was limited to platform analysis and did not address user reception, which could be investigated in future research.